Relevance of Strategic Planning Process, Organizational Ambidexterity Organizational Capabilities and Decision-Making Style Hotels Performance - ALHAWAMDEH, MAHMOUD MUSTAFA MAHMOUD (The journal of contemporary issues in business and government, 2021)
In the uncertain environment in the tourism sector especially in Arab Middle East countries, Jordan has been affected by many internal factors such as economic crisis which has threatened the political instability and external factors such as wars in neighboring countries. In order to adapt with these shift in the hotel’s sector, they should integrate strategic planning (SP) to the organization of its processes in order to make a better projection for the future. The aim of this research is to elucidate the “black box” connecting strategic planning process and organizational ambidexterity via establishing possible intervening factors. In order to guarantee a significant degree of planning practices, only three, four, and five-star hotels were targeted for data collection for the research. Data were collected from employees of 3 stars and 4 star hotels. IBM SPSS and AMOS software were used to interpret and summarize the data collected as well as to determine the effects of moderation-mediation, hence descriptive statistical techniques was employed to determine the frequency, percentage, means and standard deviation of the respondents. The findings revealed that hotel performance matters. The result also revealed that strategic planning amongst others enhance hotel performance and organization that utilize these constructs have a clear purpose and focus which drive them to optimum productivity.